ANALISIS STRATEGI PEMASARAN PAKET WISATA DALAM MENARIK MINAT KONSUMEN ( STUDI KASUS BIRO BONITA UMROH TOUR AND TRAVEL ) - Titta Putri Dentiyana; Andis Febrian (Jurnal Ekonomi dan Bisnis, 2025)
This research is motivated by a lack of human resources (HR) so that companies do not focus on marketing tour packages either in terms of social media promotion or directly, as evidenced by the decline in the number of tour package sales every year. The research method that the author used in writing this thesis is a qualitative method, the aim of this research is to find out and analyze the marketing strategies for tour packages that must be carried out to attract consumer interest in the Bonita Umrah Tour and Travel Bureau and to find out what are the inhibiting factors in marketing tour packages, where data collection techniques are carried out through interviews, observation and documentation, while the data analysis techniques used in this research are SWOT analysis, IFAS and EFAS matrices, SWOT matrices and score weight table analysis. The results of this research show that the analysis of tourism package marketing strategies in increasing consumer interest in Bonita Umroh Tour And Travel using SWOT analysis is a strategy of strengths and threats, namely with a score of 2.96. The strategy that companies can use is to utilize their strengths to face existing threats. The inhibiting factor faced by the company is the lack of human resources (employees) who understand and comprehend the creation and marketing of tour packages, and the company is more focused on marketing Umrah packages so that the marketing of tour packages is not optimal.